ANALISIS BEBAN KERJA DAN KEBUTUHAN PEGAWAI SEKSI PENGELOLAAN BIDANG GURU DAN TENAGA KEPENDIDIKAN DINAS PENDIDIKAN PROVINSI JAWA BARAT - Inggit Permatasari (Jurnal Tata Kelola Pendidikan, 2021)
The research background is caused phenomenon that shows the imbalance of workload in The Management Section, namely work time exceeding the specified work time and uneven division of labor. The research objectives are : (1) Identifying job descriptions and work products produced by employees, (2) Measuring  employee workload, (3) Calculating employee needs based of workload analysis in the management section. The method used is descriptive research method using a qualitative approach. The results of the study indicate that there are job descriptions and work products that have not been listed in the Employee Work Target and Employee Position Analysis. After measuring the workload 2 positions in The Management Section the respective work volumes were obtained including the Analyst Needs Educators and Education Personnel have a work volume of 11543 and Education Personnel Data Manager has a work volume of 8001. The imbalance is in the form of excess or lack of employees. Ideally the position of the Analyst Needs Educators and Education Personnel filled by 10 people with the number of available employees, namely 4 people, so that in this position there is a shortage of 6 employees. Education Personnel Data Manager filled by 7 people while the existing employees as many as 2 people lack of employees as many as 5 people. The research implication is that the data produced can be used as a reference in human resource planning. The research recommendations are first to re-analyze the Employee Work Target (SKP) and Employee Position Analysis (Anjab) to complete the job descriptions and products that have not been listed. Second, institutions need to carry out an analysis of workload in determining the number of employees so as to reduce the possibility of excessive workload or less. Third, to cover lack of employees in position can be done through seconding honorary employees.